Returning to Work on Chef with Graves’ Disease: A Case Report - Abadiyah, Izzatul; Soemarko, Dewi Sumaryani (Occupational and Environmental Medicine Journal of Indonesia, 2025)
Background Graves’ disease has adverse effects on quality of life, because of somatic psychiatric symptoms and an inability to work. Chefs face many occupational hazards that can aggravate certain medical conditions, worsen the disease, and pose safety risks at work. This case report aims to assess the returning-to-work evaluation and program for a chef with Graves’ disease. Case Description A forty-seven-year-old Indonesian male who was diagnosed with Graves’ disease from characteristic clinical features and biochemical abnormalities was admitted to the hospital with shortness of breath. TSH concentration was 0.001mU/L, FT4 concentration was 2.85 ng/dL, hemoglobin level was 10.6 g/dL, and thrombocyte level was 85,000mcL. The patient was a chef in a western food restaurant for eight years and exposed to several hazards related to health conditions, such as physical (hot and high humidity environment), chemical (kitchen smoke, carbon dust, allergens, and irritants from spices and foods), ergonomic (long time standing), and psychosocial (complaints from discontented customers). The return-to-work assessment on this worker was performed using the Seven Steps of Return-to-Work Evaluation Method issued by the Indonesian Occupational Medicine Association (IOMA), taking into account capacity, risk, and tolerance. Summary This worker suffers from Graves' disease, which can be exacerbated by work. The fit-to-work status was temporarily unfit to work as a chef and required a job adjustment upon returning to work.